PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAAN PELANGGAN PADA THE LUXTON HOTEL BANDUNG - Sesunan, Yunia Silvia (Jurnal Keuangan dan Perbankan Syariah, 2020)
Service excellent is a key determinant factor to assess whether the services are in accordance with the customer expectation. The Luxton Hotel Bandung required to fulfill the criteria of customer’s decision to become the first chosen by customer. The factors as follows ; tangible, reliability, responsiveness, assurance and empathy . The objectives of this study is to examine the level of customer’s satisfaction towards the services by The Luxton Hotel Bandung. This research conducted by 100 respondent which stay overnight in The Luxton Hotel Bandung. Based on the result used multiple regression shows that Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5) significant simultaneously to consumer’s satisfaction. The independent variables affect the customer’s decision to stay at the hotel shown by the coefficient of determination R2 = 0,653 or 65,30% independent variables affect to customer’s decision to stay at The Luxton Hotel Bandung and the remaining 34,70% affect by other factors.